1980
DOI: 10.2527/jas1980.514949x
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamo-Pituitary Gonadotrophic Axis of Suckled and Nonsuckled Dairy Cows Postpartum

Abstract: The objective was to determine whether the suckling-induced delay in return to estrus postpartum could be explained by changes in hypothalamic LHRH content or ability of the pituitary to release LH and FSH in response to LHRH or 59 mM K+ in vitro. In addition, serum concentrations of several other hormones were measured. Nine Holstein cows were suckled ad libitum by two calves and milked by machine twice daily and eight were milked by machine only from calving until slaughter on day 14 postpartum. On day 13 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 18 publications
1
21
0
1
Order By: Relevance
“…Since the postovariectomy elevation of plasma LH is impaired by suckling as well [13,18,19,27,38], it seems likely that suckling acts to inhibit the release of LHRH from the ME. Previous studies using only intact, lactating animals have reported a significant decrease [29,38] or, as observed in the present study, no change [7,32] in the concentration of immunoreactive LHRH in the hypothala mus as a result of the suckling stimulus. These results de monstrate that evaluation of the effects of suckling on hypo thalamic LHRH may require the use of a model (such as the ovariectomized rat) which will produce more extreme, measurable changes.…”
Section: Discussionmentioning
confidence: 33%
See 1 more Smart Citation
“…Since the postovariectomy elevation of plasma LH is impaired by suckling as well [13,18,19,27,38], it seems likely that suckling acts to inhibit the release of LHRH from the ME. Previous studies using only intact, lactating animals have reported a significant decrease [29,38] or, as observed in the present study, no change [7,32] in the concentration of immunoreactive LHRH in the hypothala mus as a result of the suckling stimulus. These results de monstrate that evaluation of the effects of suckling on hypo thalamic LHRH may require the use of a model (such as the ovariectomized rat) which will produce more extreme, measurable changes.…”
Section: Discussionmentioning
confidence: 33%
“…Previous studies have suggested that suckling reduces the release of LH from the pituitary by lowering the concentration of lu teinizing hormone releasing hormone (LHRH) In the hypo thalamus [29,38]. However, recently reported data in the ewe [32] and cow [7] have failed to detect a significant differ- Ovariectomy has been reported to cause a significant decrease in the concentration of LHRH present in the hypo thalamus [1, 5,8,17,23,41] while plasma LH levels are markedly increased [5,8,23,41]. The reduction in hypotha lamic LHRH content is believed to reflect an increased rate of release which exceeds the rate of LHRH synthesis.…”
mentioning
confidence: 79%
“…This can be explained by the fact that suckling tends to suppress growth of follicles (Carter et al, 1980) and blocks ovulation (Spicer and Echternkamp, 1986). Moreover, the frequency and amplitude of LH peaks, together with reduced sensitivity of the pituitary to LH-releasing hormone may be the cause of inhibition of ovulation in suckled cows (Carruthers et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Episodic secretion of GnRH from the hypothalamus regulates the pulsatile pattern of LH release from the pituitary [2]. Although hypothalamic content of GnRH is not affected by suckling status [3][4][5], GnRH concentrations in the hypophyseal portal system are suppressed by suckling [6]. Therefore, even though anterior pituitary content of LH is replenished in suckled cows within 2-3 wk after parturition [7], secretory patterns of LH remain suboptimal for the development of preovulatory follicles [8,9].…”
Section: Introductionmentioning
confidence: 92%